0057 How does a structured debriefing framework affect the quality of debriefing process for undergraduate interprofessional simulation?. (2nd November 2015) - Craft, Zachary; Franklin, Danielle; Smith, Susanne; Roberts, Martin; Endacott, Ruth; Gale, Thomas
Abstract : Background/context: TeamGAINS is a framework for structuring team-based simulation debriefs. 1 Postgraduate trainee perception of TeamGAINS suggested it could be a useful framework. 1 We aimed to evaluate how TeamGAINS affects the quality of debriefing in undergraduate interprofessional simulation. Methodology: One faculty member from each course jointly debriefed interprofessional simulation sessions for final year nursing and medical students. 20 sessions were run prior to training debriefers in the TeamGAINS framework and 20 afterwards. Debriefs were video recorded. Two independent, trained assessors, blinded to session sequence, used the Debriefing Assessment for Simulation in Healthcare (DASH) rater version 2 to evaluate videoed debrief quality. DASH elements 2–6 were recorded, element 1 (e stablishes an engaging learning environment ) was not recorded because session introductions were not videoed. One assessor then recorded compliance with the content and order of the TeamGAINS steps and video replay frequency and duration in post-training debriefs. Compliance was not recorded pre-training because debriefers may have already been implementing steps without knowledge of the framework, resulting in false positives. Results/outcomes: 19 pre- and 18 post-training debriefs were analysed. Moderate interrater reliability was observed for DASH means (Intraclass Correlation Coefficient = 0.428). Mean DASH ratings significantly improved pre-post-training (pre: 3.97, post: 4.87, p < 0.001) as did elements 3, 4, 5 and 6 ratings (p < 0.005 in all cases). 7 variations of TeamGAINS order occurred post-training. A moderate negative correlation for duration of video replay with DASH mean rating was observed post-training though this was not statistically significant (r = –0.417, p = 00.85). Conclusions and recommendations: Training debriefers in the TeamGAINS framework improved overall DASH ratings of debrief quality. Longer use of video replay may not improve debriefing quality. Funded through a Collaborative Teaching Development Grant awarded by the Higher Education Academy. References: Kolbe M, Weiss M, Grote G, Knauth D, Dambach M, Spahn DR, et al . TeamGAINS: a tool for structured debriefings for simulation-based team trainings. BMJ Qual Saf. 2013;22(7):541–53 Simon R, Raemer DB, Rudolph JW. Debriefing assessment for simulation in healthcare – rater version, long form . Boston, MA: Center for Medical Simulation, 2010